Study of the Method of Electro-Crystallization and the Study of Effective Factors in the Production of Nanostructures in this Method - Sherzaman Hamidi; Bashirullah Safi; Abdul Waheed Waheed (Global Writing Academica Researching and Publishing, 2022)
Due to the fact that nanostructures have very high-performance capabilities in various scientific and industrial fields, during the last few years these nanostructures have become available for production in order to produce particulate matter with appropriate composition and distribution. One of the focal points of the current study is the exploration of a number of different researches carried in the field. Considering that the method of electro crystallization compared to other methods available for the production of nanostructures is relatively new, this study gives a brief overview of the effective methods of electro crystallization and the effective parameters in the production of nanostructures produced at high speed, the integrity of materials and the sustainability of particles produced, the diversity in production, low cost and simple use of equipment. The findings of the study are presented that explore the effective parameters in the production of nanostructures, the voltage applied, the time it takes, the concentration of electrolyte and the temperature. The findings further show that the factors of change in voltage and oxidation has the greatest effect on the morphology and particle size. Moreover, the increase in voltage is due to the rapid increase in the speed that leads to the production of resistive crystalline sediments.